Design of a high-force-density tubular motor - Galea, Michael; Buticchi, Giampaolo; Empringham, Lee; De Lillo, Liliana; Gerada, C. (IEEE, 2014)
This paper deals with the design, construction and experimental verification of a high force density, tubular, linear, permanent magnet motor, driven from a high power density matrix converter for an aerospace application. The work also describes the implementation and experimental verification of a novel, thermal management technique for the phase windings of electrical machines. The technique introduces a higher thermal conductivity path between the centre of the slot and the cooling arrangement, thus increasing the heat flow away from the slot centre. An introduction to the design of the motor is first given, after which an introduction to the technique is presented. A study of how the implementation of the technique affects motor performance is then presented. A detailed overview of the construction aspects is highlighted and finally, experimental validation is used to illustrate the comparison between the predicted results and the measured results, obtained from an instrumented, test rig.